INOVASI KERAJINAN KERTAS DI THE GRIYA LOMBOK UNTUK MENDUKUNG PARIWISATA RAMAH LINGKUNGAN MENUJU NET ZERO EMISSION INDONESIA 2060 - Sanjaya, I Gusti Lanang Putra (Institut Agama Hindu Negeri Gde Puda Mataram, 2025)
Net Zero Emission is a condition where the amount of greenhouse gas emissions released does not exceed the amount of emissions that can be absorbed by the earth. The program aims to minimize environmental pollution that has the potential to cause global warming and other natural disasters. One of the efforts to support the program is to apply paper craft innovations found at The Griya Lombok, which recycle paper into high-quality paper craft art. In addition, the application of these paper craft innovations in Indonesia can also support environmentally friendly tourism. To achieve this, the role of young intellectuals is needed to disseminate and provide education about the positive impact of paper craft innovation at The Griya Lombok on the environment. In order to increase the smoothness of achieving environmentally friendly tourism and Net Zero Emission in Indonesia, support from the Indonesian government is also needed. This scientific paper aims to find out the potential of paper crafts in supporting the concept of environmentally friendly tourism and Indonesia's Net Zero Emission 2060 program, as well as the role of young intellectuals to achieve these goals. The author uses qualitative research methods to collect information on site directly. The recycling of waste paper into craft art can reduce tree cutting, which is one of the causes of more greenhouse gas emissions than the earth can absorb. In addition, support from the Indonesian government for the paper craft industry can facilitate the path to successfully achieving the concept of environmentally friendly tourism and the Net Zero Emission program in Indonesia.